Respuesta :

Answer:

log8 (X/Y

x = -4

Step-by-step explanation:

log8 X = log8 Y

= log8 (X/Y)


3^(x-1) = 1 / 243

3^(x - 1) =  1 / 3^5

3^(x - 1) = 3^(-5)

x - 1 = -5

x = -4

Answer: log₈[tex](\frac{X}{Y} )[/tex]

Step-by-step explanation:

log₈X - log₈Y

log rules say that subtraction becomes division when combining into one log

log₈[tex](\frac{X}{Y} )[/tex]

********************************************************************

Answer: -4

Step-by-step explanation:

3ˣ⁻¹ = [tex]\frac{1}{243}[/tex]

3ˣ⁻¹ = 3⁻⁵

x - 1 = -5

  +1   +1

x     = -4

********************************************************************

Answer: [tex]\frac{5}{3}[/tex]

Step-by-step explanation:

[tex](\frac{1}{6})^{x - 5} = 36^{x}[/tex]

6⁻¹⁽ˣ⁻⁵⁾ = 6²⁽ˣ⁾

-1(x - 5) = 2(x)

-x + 5 = 2x

+x         +x

       5 = 3x

       [tex]\frac{5}{3} = x[/tex]

********************************************************************

Answer:  0

Step-by-step explanation:

log₂ 1 = x

       1 = 2ˣ

     2⁰ = 2ˣ

      0 = x